Fazenda da Juta/SP: uma trilha entre o rural e o urbano: trajetória de luta e resistência no assentamento de um povo - Ferreira, Deocleciana (2018)
This study reconstructs the transformation of an area in the eastern periphery of São Paulo from rural settlement to urban neighborhood. Emblematically, the area carries the name of Fazenda da Juta (Juta Farm), after a crop widely found in the region at the beginning of the 20th century, until the coffee crisis of 1929. During this process of transformation – from an area initially settled by Italian migrants dedicated to fruit farming, and later by Brazilian migrants from the drought-ridden Northeast of the country – the workforce faced conditions of extreme poverty that would give rise to struggles on two fronts: individually for work, and collectively, with their family and neighbors, for the urbanization of the territory they occupied. This ethnographic and documentary study recaptures the lived spaces of this history and collects stories, testimonies and memories to reconstruct the political struggles of the Fazenda da Juta Movement, and their consequences, over four decades. The study primarily focuses on the period from 1960 to 1990, although it traces shifts in land ownership and development processes back to the nineteenth century. This reconstruction shows these struggles among a segment of the population to be a legitimate expression of democratic, popular strength capable of producing continual counter-hegemonic mobilization for access to land and housing. The occupiers of Fazenda da Juta are the protagonists of this story, who, besides building their own homes, organized collectively to demand the provision of urban and social infrastructure in their neighborhood. This study draws on documentary evidence and testimonies to show that a popular neighborhood in the metropolis of São Paulo was urbanized primarily as a result of processes of social mobilization, while the State failed to meet its obligations to provide adequate living conditions in the city’s popular settlements